A educação popular na práxis do ProJovem Campo - Saberes da Terra no Espírito Santo - Ferreira, Maria Geovana Melim (2015)
This study systematizes experiences/ consolidates in the practice of educators of the Program ProJovem Campo – Saberes da Terra that worked at the 29 classes distributed among 19 cities of the state of Espírito Santo, Brazil. It’s goal was to reflect about the theoretical and methodological challenges that were brought up at the practices in the formative path lived and the contributions that were produced. Based on the theoretical input of popular education and countryside education, placing for analysis what was possible to experience and looking forward to theorize about what was materialized at the practice of integration from the pedagogical interchange that had as educational principles the work and the research. The methodological choice of systematization is admitted as a way to review the practice and theorize about it, using the documental analysis and the primary sources provided by educators. In between the many results obtained, the collective processes stood out, pointing out contradictions in the rushed way EJA (Education for Youth and Adults) was offered, built as discontinuous actions of compensating politics. As elements of the proposal, the results show that the work and the research were taken as an educational principals of the pedagogical process, and were built on a solid experience of curricular integration, from actions developed at the pedagogical interchange, although not all of the educators acknowledge these concepts. The self-organization emerges as a fundamental element in the perspective of articulation between theory and practice, labor and intellectual work and of the non-hierarchical learning relations, capable of producing significant changes, not only in its pedagogical praxis, but also in various life experiences. However, the study points out the non-continuity of offer of the program as a public policy for the education of youth and adults of the countryside